Lifetime reduction of surface states at Cu, Ag, and Au(111) caused by impurity scattering - Heers, Swantje; Mavropoulos, Phivos; Lounis, Samir; Zeller, Rudolf; Blügel, Stefan (PHYSICAL REVIEW B, 2012)
We present density-functional results on the lifetime of the (111) surface state of the noble metals. We consider scattering on the Fermi surface caused by impurity atoms belonging to the 3d and 4sp series. The results are analyzed with respect to film thickness and with respect to separation of scattering into bulk or into surface states. While for impurities in the surface layer the overall trends are similar to the long-known bulk-state scattering, for adatom-induced scattering we find a surprising behavior with respect to the adatom atomic number. A plateau emerges in the scattering rate of the 3d adatoms, instead of a peak characteristic of the d resonance. Additionally, the scattering rate of 4sp adatoms changes in a zigzag pattern, contrary to a smooth parabolic increase following Linde's rule that is observed in bulk. We interpret these results in terms of the weaker charge screening and of interference effects induced by the lowering of symmetry at the surface.